2021
DOI: 10.1021/acssensors.0c02346
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Complex Samples with Molograms of Low-Affinity Binders

Abstract: In vitro diagnostics relies on the quantification of minute amounts of a specific biomolecule, called biomarker, from a biological sample. The majority of clinically relevant biomarkers for conditions beyond infectious diseases are detected by means of binding assays, where target biomarkers bind to a solid phase and are detected by biochemical or physical means. Nonspecifically bound biomolecules, the main source of variation in such assays, need to be washed away in a laborious process, restricting the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Reproduced with permission. [ 144 ] Copyright 2021, American Chemical Society. https://pubs.acs.org/doi/10.1021/acssensors.0c02346.…”
Section: Advanced Sensing Systems and Devices For Monitoring Of Cell ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 144 ] Copyright 2021, American Chemical Society. https://pubs.acs.org/doi/10.1021/acssensors.0c02346.…”
Section: Advanced Sensing Systems and Devices For Monitoring Of Cell ...mentioning
confidence: 99%
“…showed that diffractometric measurements are insensitive to unsought nonspecific bindings and, therefore, allow the detection of unprocessed, complex samples such as plasma. [ 144 ] They used focal molography, a technique used to visualize molecular binding on a coherent pattern of binding sites (molograms) on a single‐mode optical waveguide (Figure 10b). The molographic designs are a combination of ridges and grooves containing high‐affinity probes for extracellular protein domains and a passivated layer, respectively.…”
Section: Advanced Sensing Systems and Devices For Monitoring Of Cell ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we introduce a generalizable, quantitative live-cell assay for the analysis of cytosolic PPIs, which is based on the working principle of focal molography. Focal molography is an optical system for molecular interaction analysis that is insensitive to nonspecific molecular interactions . This unique property is achieved by the arrangement of binding sites into a regular ( i.e.…”
mentioning
confidence: 99%
“…31−33 Focal molography is an optical system for molecular interaction analysis that is insensitive to nonspecific molecular interactions. 34 This unique property is achieved by the arrangement of binding sites into a regular (i.e., coherent) pattern, termed the "mologram" (Figure 1a). The molographic pattern alternates ridges, which are usually made to contain high-affinity probes, and nonfunctional grooves, which act as an intrinsic reference.…”
mentioning
confidence: 99%